Bakounine en Italie en 1864. Souvenirs. Trad. du russe par M. Stromberg. [Partie I et] suite (Paris, 1898)
La Revue socialiste, Année XIV, 158 - tom. 27 - pag. 175-181 et 161 - tom. 28 - pag. 595-603.